Evaluasi Peresepan Antibiotik pada Pasien ISPA Pediatri Metode ATC/DDD - Anak Agung Pradnya Paramitha Vidiani; Livania Indri Aswara; Madyo Adrianto; Anisa Devi Kharisma Wibowo (Jurnal Kesehatan Amanah, 2023)
Acute Respiratory Infections (ARI) are infectious diseases that cause the highest mortality rate in children. Antibiotics are administered to ARI patients if the infection is caused by bacteria. Excessive use of antibiotics increases the risk of resistance and irrational antibiotic use. Efforts to prevent antibiotic resistance and irrational use include evaluating antibiotic utilization based on WHO recommendations, specifically using ATC/DDD classification system and the DU90% method. This study aims to determine the antibiotic utilization profile, DDD/1000 patient-days, and DU90% among pediatric ARI from January 2022 to December 2023. This study employs a quantitative research method with retrospective data collection. The results indicate that the highest antibiotic class used was penicillin (98%), with Amoxicillin 500 mg being the most commonly prescribed antibiotic (98%). The most prevalent ARI diagnosis was Acute Pharyngitis (J.02) (66.1%). The most frequently used dosage form was syrup (54.7%), and the average duration of therapy was 3–5 days. The total antibiotic consumption was 137.4 DDD/1000 patient-days, with antibiotics included in the DU90% segment being Amoxicillin 500 mg (102.3 DDD/1000 patient-days) and Amoxicillin 250 mg (21.6 DDD/1000 patient-days). This study highlights that the most widely used antibiotic in terms of quantity was Amoxicillin 500 mg (102.3 DDD/1000 patient-days).